Asia shock : horror and dark cinema from Japan, Korea, Hong Kong, and Thailand / by Patrick Galloway ; illustrations by Greg Lofrano. - Galloway, Patrick. (Stone Bridge Press, 2006)
"Asian Extreme cinema is hot, and this book celebrates all its gory glory. Patrick Galloway, who last looked at samurai films in Stray Dogs & Lone Wolves: The Samurai Film Handbook, now takes on Asian masters of suspense, exploitation, the supernatural, and bone-chilling, blood-curdling horror. This critical guide contains over 50 reviews of fans' and critics' favorites ranging from classics like Nakagawa's Ghost of Yotsuya to contemporary cutting-edge films by Takashi Miike and Park Chan-wook. Included are viewing tips, cultural backgrounds, and genre overviews."--Jacket.